2022
DOI: 10.1039/d2bm00550f
|View full text |Cite
|
Sign up to set email alerts
|

An Ag2S@ZIF-Van nanosystem for NIR-II imaging of bacterial-induced inflammation and treatment of wound bacterial infection

Abstract: Bacterial diseases pose a serious threat to human health. Continued development of precise diagnostic methods and synergistic therapy techniques for combating bacteria are needed. Herein a hybrid nanosystem (Ag2S@ZIF-Van NS)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Furthermore, Huang et al constructed a self-assembled NIR-II emitting hybrid nanoplatform called Ag 2 S@ZIF-Van nanostructure, which incorporated Zn 2+ , vancomycin, and Ag 2 S QDs. 426 Ag 2 S@ZIF-Van enabled precisely targeted fluorescence imaging of bacterial inflammation in vivo and promoted antibacterial and wound healing effects.…”
Section: Pathogen-induced Inflammation Imagingmentioning
confidence: 99%
“…Furthermore, Huang et al constructed a self-assembled NIR-II emitting hybrid nanoplatform called Ag 2 S@ZIF-Van nanostructure, which incorporated Zn 2+ , vancomycin, and Ag 2 S QDs. 426 Ag 2 S@ZIF-Van enabled precisely targeted fluorescence imaging of bacterial inflammation in vivo and promoted antibacterial and wound healing effects.…”
Section: Pathogen-induced Inflammation Imagingmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are emerging porous materials with large surface area, metal-containing clusters, and tunable structure, making them highly attractive as powerful platforms for diverse applications. Zeolitic imidazolate frameworks (ZIFs) composed of transition metal cations and imidazolate ligands can exhibit Fenton or Fenton-like reaction activity by introducing cobalt or other metallic elements as a metal node. , In particular, a cobalt-based ZIF (ZIF-67) has been developed for antibacterial use owing to the favorable biocompatibility and acid degradation capacity of this material. Recently, Chen et al synthesized a series of ZIF-67 with different morphologies and sizes and demonstrated that these nanostructures exhibited enhanced antibacterial activity against Saccharomyces cerevisiae. Importantly, the large surface area of ZIF nanosheet materials facilitates the access of substrate molecules to surface active sites with smaller diffusion barriers than those of bulk ZIFs. , Thus, compared to conventional bulk ZIFs, ZIF nanosheets offer better potential for biocatalytic applications. , …”
Section: Introductionmentioning
confidence: 99%
“…32−34 Zeolitic imidazolate frameworks (ZIFs) composed of transition metal cations and imidazolate ligands can exhibit Fenton or Fenton-like reaction activity by introducing cobalt or other metallic elements as a metal node. 12,35 In particular, a cobalt-based ZIF (ZIF-67) has been developed for antibacterial use owing to the favorable biocompatibility and acid degradation capacity of this material. 36−40 Recently, Chen et al 41 synthesized a series of ZIF-67 with different morphologies and sizes and demonstrated that these nanostructures exhibited enhanced antibacterial activity against Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, most nanoparticle platforms cannot be biodegraded in vivo , posing potential toxicity to organisms. 14–17…”
Section: Introductionmentioning
confidence: 99%
“…13 However, most nanoparticle platforms cannot be biodegraded in vivo, posing potential toxicity to organisms. [14][15][16][17] The primary goal of this study is developing biodegradable nanoassemblies and to explore their chemo/CDT/PTT effects against bacterial infection. Cinnamaldehyde (CA) is a significant component in cinnamon, and possesses an antibacterial effect against microorganisms.…”
Section: Introductionmentioning
confidence: 99%